Burden of baseline resistance of Mycobacterium tuberculosis to fluoroquinolones and second-line injectables in central India. (31st January 2020) - Desikan, Prabha; Panwalkar, Nikita; Chaudhuri, Shreya; Khan, Zeba; Punde, Ram Prakash; Pauranik, Ankur; Mirza, Shaina Beg; Ranjan, Rajeev; Anand, Sridhar; Sachdeva, K S
Abstract: Background: Drug-resistant TB is a serious public health problem in India. Pre-existing resistance to fluoroquinolones (FQs) and second-line injectable drugs (SLIDs) in strains of Mycobacterium tuberculosis (MTB) resistant to rifampicin (RIF) and/or isoniazid (INH) contributes to treatment failures and consequent transmission of drug-resistant TB. A baseline assessment of resistance of MTB to FQs and SLIDs may help guide policies to further improve management of drug-resistant TB in India. This study aims to determine the prevalence of resistance to FQs and SLIDs among MTB strains having RIF and/or INH resistance in central India. Method: A total of 1032 smear positive sputum samples were subjected to line probe assay (GenoType MTBDRsl version 2) to test for resistance to FQs and SLIDs, according to the integrated diagnostic algorithm of the revised national TB control programme. Results: Of 1032 samples, 92 (8.91%) were not interpretable and hence excluded, 295 (31.38%) were resistant to FQs alone, 13 (1.38%) were resistant to SLIDs alone, 15 (1.59%) were resistant to both FQs as well as SLIDs and 617 (65.63%) were sensitive to both FQs and SLIDs. The most common mutations in gyr A and gyr B genes were observed at codons D94G and E540V, respectively. Mutations at codon A1401G in rrs genes and in the C-14 T region of eis genes were most frequently observed. Conclusion: High levels of FQ resistance points towards indiscriminate use of this class of drugs. Regulation for judicial use of FQs is an urgent requirement.